Utilization of fruit extract as acidulant on physicochemical and sensory properties of cottage cheese with addition calcium chloride - Eva amelia Reza Hanum; Ratna Yulistiani; Ulya Sarofa (Asia Pacific Network for Sustainable Agriculture, Food and Energy (SAFE-Network), 2022)
This research aimed to determine the effect of the type of fruit extract as an acidulant and calcium chloride concentration on the physicochemical and organoleptic characteristics of cottage cheese. The research used a completely randomized design (CRD) with two factors and three repetitions. Data analysis using ANOVA was continued with Duncan's multiple range test (DMRT) at the 5% confidence level. The first factor was the type of fruit extract as an acidulant (A) which consists of three levels, that was wuluh starfruit 30% (A1), lime 7.5% (A2), lemon 7.5% (A3), and concentration of calcium chloride (B) which consists of three levels (0.01% (B1), 0.02% (B2), and 0.03% (B3)). Parameters observed included pH, titratable acidity, moisture content, yield, calcium content, fat content, protein content, ash content, hardness, and organoleptic analysis including taste, aroma, color, and hardness. The results of the treatment of fruit extract as an acidulant and calcium chloride concentration significantly affected the pH value, titratable acidity, yield, moisture content, calcium content, fat content, protein content, ash content, hardness, and organoleptic tests. Cottage cheese treated with 7.5% lemon acidulant and 0.03% calcium chloride was the best treatment with pH 5.05, titratable acidity 3.25%, moisture content 60.80%, yield 22.05%, calcium 1.16 mg/100 g, ash content 2,13%, fat content 0.090%, protein content 18.87%, hardness 14.87 gf, and taste not sour, not fruity, quite white, and not hard.d to determine the effect of the type of fruit extract as an acidulant and calcium chloride concentration on the physicochemical and organoleptic properties of cottage cheese. The research used a completely randomized design (CRD) with two factors and three repetitions to produce 27 treatments. Data analysis using ANOVA was continued with Duncan's new multiple range test (DNMRT) at a significance level of 5%. The first factor was the type of fruit extract as an acidulant (A) which consists of three levels. that was wuluh starfruit 30% (A1). lime 7.5% (A2). lemon 7.5% (A3) and concentration of calcium chloride (B) which consists of three levels (0.01% (B1). 0.02% (B2). and 0.03% (B3)). Parameters observed included pH. titratable acidity. water content. yield. calcium. fat content. protein content. ash. hardness and organoleptic analysis including taste. aroma. color. and hardness. The results of the treatment of fruit extract as an acidulant and calcium chloride concentration significantly affected the pH value. titratable acidity. yield. water content. hardness. yield. calcium. fat content. protein content. ash. and organoleptic tests. Cottage cheese treated with 7.5% lemon acidulant and 0.02% calcium chloride was the best treatment with pH 5.14. titratable acidity 2.99%. water content 62.04%. yield 24.98%. calcium 1.152 mg/100 g. 0.074% fat. 17.89% protein. 12.45 of hardness. and taste not sour. not fruity. moderate yellowish-white color. and not hard.